Examination of leisure sports alternatives provided by higher education institutions - Pfau, Christa (Applied Studies in Agribusiness and Commerce, 2015)
It is one of the main duties of sports in higher education to provide health conscious and sports-loving managers to the society. University years are a good opportunity to do sports in an organised framework, as well as lifestyle consultancy and to make use of the preventive function of sports. In this environment, the approach of students can still be shaped within a formal framework and their level of interest towards sports can still be increased. Furthermore, they can be motivated and become committed to sports if they have positive experiences. The aim of my analysis is to explore and describe the characteristics, peculiarities and current situation of higher education leisure sports. In this study, I present the results of the analysis of data collected with the first eight questions of the situation assessment part of the questionnaire survey. More specifically, I examined the evaluation of leisure sports activities, free sports opportunities and the branches of sports in which these are provided. I was also looking to find out where these sports opportunities are available for students inside or outside the institution and who they are organised and managed by. At the same time, I examined sports opportunities whose costs are paid by the student and analysed which branches of sports are available. Based on my results, I concluded that the sports opportunities of students are especially good according to the managers. This statement confronts the research findings which suggest that the sports activity of students is very low.JEL code: Z20